2017
DOI: 10.21474/ijar01/3692
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Vitamin D Levels in Egyptian Adults With Chronic Primary Immune Thrombocytopenia: A Single Center Study.

Abstract: Objectives:Immune thrombocytopenia (ITP) is a disorder characterized by immune-mediated accelerated platelet destruction and suppressed platelet production. Low vitamin D levels have been found in several autoimmune diseases, such as rheumatoid arthritis, SLE. The mechanisms underlying the link between vitamin D with autoimmunity are not completely understood. No currently available studies about vitamin D status in primary ITP patients. Aim: To evaluate vitamin D levels in patients with primary chronic ITP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(35 reference statements)
2
1
0
Order By: Relevance
“…In the present study, we have found a significantly lower mean levels of vitamin D among ITP cases compared to healthy control group, (18.85±10.87 ng/ml) vs (32-100 ng/ml) ( 14) respectively with p-value <0.001. These findings were in accordance with the findings of Soliman et al (8) and Mu et al (15). Our study has shown that the blood level of vitamin D in chronic ITP was higher than acute ITP although not statistically However, our study have some limitations.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, we have found a significantly lower mean levels of vitamin D among ITP cases compared to healthy control group, (18.85±10.87 ng/ml) vs (32-100 ng/ml) ( 14) respectively with p-value <0.001. These findings were in accordance with the findings of Soliman et al (8) and Mu et al (15). Our study has shown that the blood level of vitamin D in chronic ITP was higher than acute ITP although not statistically However, our study have some limitations.…”
Section: Discussionsupporting
confidence: 94%
“…The mean age of ITP patients in our study was 39.90 ± 16.11 years, this was higher than that described by Cines and Bussel (10) In the present study, we did not find a significant correlation between vitamin D levels and age, sex or disease duration in ITP patients. This finding is in line with the results of a study by Soliman et al (8). Also other studies did not find a significant correlation between vitamin D level and age or disease duration in SLE (12) and rheumatoid arthritis (13) patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation